From Secular Capitalism to Spiritual Balance: The Relevance of Naquib Al-Attas’s Vision in Contemporary Economic Thought - Rosyidah, Rihadatul Izza; Riza, Ira Febriliana Dewi; Meldona, Meldona; Amaliah, Churil (Economica: Jurnal Ekonomi Islam, 2023)
The current capitalist economic system, rooted in secular Western ideology, has evolved beyond a market mechanism into a pervasive lifestyle that emphasizes materialism, autonomy, and human-centered progress. However, this system fundamentally contradicts Islamic teachings, which integrate worldly and spiritual life under divine sovereignty. This study employs a descriptive-analytical method to critically examine capitalism through the lens of Syed Muhammad Naquib Al-Attas’s thought. Al-Attas argues that capitalism leads to moral disintegration and spiritual alienation by detaching economic behavior from its metaphysical roots. As a corrective, he advocates for a return to an authentic Islamic worldview grounded in tawhid and adab. The findings suggest that addressing capitalism’s failures requires adopting a balanced path—one that harmonizes material well-being with spiritual fulfillment. Al-Attas’s vision, centered on the Islamization of knowledge, offers a transformative foundation for developing an Islamic economic system that is both ethically grounded and socially just.